A novel 2-step ALD route to ultra-thin MoS2 films on SiO2 through a surface organometallic intermediate. Issue 2 (20th October 2016) - Cadot, Stéphane; Renault, Olivier; Frégnaux, Mathieu; Rouchon, Denis; Nolot, Emmanuel; Szeto, Kai; Thieuleux, Chloé; Veyre, Laurent; Okuno, Hanako; Martin, François; Quadrelli, Elsje Alessandra
Abstract : MoS2 monolayers by 2-step ALD: [1 st ] MLD by surface organometallic chemistry (SOMC) to molybdenum thiolate. [2 nd ] Self-smoothing annealing towards 2D MoS2 crystals. Abstract : The lack of scalable-methods for the growth of 2D MoS2 crystals, an identified emerging material with applications ranging from electronics to energy storage, is a current bottleneck against its large-scale deployment. We report here a two-step ALD route with new organometallic precursors, Mo(NMe2 )4 and 1, 2-ethanedithiol (HS(CH2 )2 SH) which consists in the layer-by-layer deposition of an amorphous surface Mo(iv ) thiolate at 50 °C, followed by a subsequent annealing at higher temperature leading to ultra-thin MoS2 nanocrystals (∼20 nm-large) in the 1–2 monolayer range. In contrast to the usual high-temperature growth of 2D dichalcogenides, where nucleation is the key parameter to control both thickness and uniformity, our novel two-step ALD approach enables chemical control over these two parameters, the growth of 2D MoS2 crystals upon annealing being ensured by spatial confinement and facilitated by the formation of a buffer oxysulfide interlayer.